A Review: Using Ionic Liquids for Lignin Extraction from Lignocellulose and High-Value Utilization - Xinyu Li; Jiming Yang; Wei He; Shuangfei Zhao; Zheng Fang; Kai Guo; Yuguang Li (Molecules, 2025)
Lignocellulose is the most abundant renewable resource in nature, providing a large supply of lignin. The efficient separation and utilization of lignin from lignocellulose can help alleviate the current shortage of fossil fuels. Ionic liquids, as green solvents, have been widely applied in the field of biorefining. However, most research has focused on the extraction and purification of cellulose, while lignin is often treated as a by-product. The high-value utilization of lignin has currently emerged as a hot topic. This review summarizes recent advances in the extraction of lignin from lignocellulose using ionic liquids and the mechanisms of lignin extraction. Additionally, it briefly discusses the applications of ionic liquids in the high-value utilization of lignin, including lignin depolymerization, modification, the preparation of lignin-based functional materials, and biofuels. This review aims to provide ideas for the extraction and high-value utilization of lignin through ionic liquids.